Frontotemporal Dementia as a Possible Manifestation of Primary Lateral Sclerosis: A Case Report and Literature Review. (4th March 2022) - Qosja, Kevin; Absar, Nicole M.; Yu, Allen T.
Abstract : Primary lateral sclerosis (PLS) is currently defined as a restricted phenotype of amyotrophic lateral sclerosis (ALS), a neurodegenerative disease with upper motor neuron (UMN) symptoms that causes slowly progressive spasticity. The diagnostic criteria of this disorder currently do not include any effects on frontal executive or other cortical functioning. We report an 84-year-old woman diagnosed with six years of PLS who also had concurrent symptoms of difficulties in language, anxiety, emotional lability, and executive function. This case, as well as previously reported cases in the literature, is an example that shows the importance of more widespread consideration for PLS in patients with UMN signs and indications of frontotemporal dementia (FTD). Increased consideration for PLS would be beneficial for many patients and positively affect treatment, especially since patients live with the disorder for longer periods than ALS.